PENGARUH LOKASI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA APARTEMEN FX SUDIRMAN RESIDENCE DI JAKARTA - Egita Tri Anggraini; Ahmad Nurhadi (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The purpose of this study was to determine the effect of location and price on purchasing decisions at FX Sudirman Residence Apartment. The method used is quantitative. The sampling technique uses the Slovin formula and a sample of 98 respondents was obtained. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are that location has a significant positive effect on purchasing decisions with a determination coefficient value of 45.7% and thehypothesis test obtained t count> t table or (8.981> 1.985). Price has a significant negative effect on purchasing decisions with a determination coefficient value of 20.0% and the hypothesis test obtained t count> t table or (- 4.892> -1.985). Location and price simultaneously have a significant effect on purchasing decisions with a regression equation Y= 23.034 + 0.543X1 - 0.141X2. The coefficient of determination value is 56.2% while the remaining 41.8% is influenced by other factors and the hypothesis test obtained the calculated F value > F table or (60.956 > 2.700).